使用普萘洛尔治疗IH的BSPD指南. (17th September 2018) - Solman, L.; Glover, M.; Beattie, P.E.; Buckley, H.; Clark, S.; Gach, J.E.; Giardini, A.; Helbling, I.; Hewitt, R.J.; Laguda, B.; Langan, S.M.; Martinez, A.E.; et al.
Abstract : Linked Article:  Solman et al. Br J Dermatol 2018;179 :582–589